Modifier for low-activity mineral powder-based all-solid waste cementing material and preparation method thereof
By adding modifiers of hydrated lime, aluminate and polymer aluminum chloride to the low-active ore powder-based all solid waste gelling material, the problem of insufficient mechanical properties was solved, and strength improvement and solid waste meeting the 42.5 grade were achieved. Efficient utilization meets construction and environmental protection needs.
Patent Information
- Application Number
- CN202411324540.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to prepare low-active ore powder-based all-solid waste gelling materials that meet the grade 42.5 by adding additional modifiers, resulting in insufficient mechanical properties and inability to meet construction and transportation requirements.
Using hydrated lime, aluminate and polymer aluminum chloride as modifiers, its 28d activity and mechanical properties are improved by mixing and adding them to low-active ore powder-based all-solid waste gelling materials.
It significantly improves the mechanical properties of the fully solid waste gelling material of low-active ore powder-based, making it reach a strength of 42.5. It is suitable for road cement stable gravel layers and mine filling, increasing solid waste utilization rate and achieving energy conservation and emission reduction.
Smart Images

Figure CN119176687A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of comprehensive utilization of solid waste and building materials, and in particular relates to a modifier for low-activity mineral powder-based all-solid waste gelling material and a preparation method thereof. Background Art
[0002] As one of the most widely used cementitious materials, silicate cement is facing the dilemma of shortage of raw materials, increasing depletion of natural ores, and high energy consumption and carbon emissions in production. At the same time, the cement industry has become an urgent problem to be solved in the development of low carbonization due to its high energy consumption, high emissions and high pollution in the production process. Using solid waste to prepare cement-based cementitious materials can not only save a large amount of natural ores, but also reduce carbon emissions and dust pollution in the cement roasting production process, which has significant economic and social benefits.
[0003] All-solid waste cementitious materials use industrial solid wastes such as granulated blast furnace slag, fly ash, desulfurized gypsum and steel slag produced by national pillar enterprises such as steel enterprises and coal-fired power generation as raw materials. Through proper processing and treatment, they form new materials with cementitious properties. They can be used in the fields of construction and road construction, and have the dual advantages of environmental protection and resource utilization. Low-activity mineral powder-based all-solid waste cementitious materials are a type of all-solid waste cementitious materials that use low-activity mineral powder as the main cementitious material. Due to the use of low-activity mineral powder, the 28d strength of the product cannot reach 42.5 levels, which is not conducive to construction and long-distance transportation.
[0004] Although the prior art also discloses methods for preparing all-solid waste cementitious materials using slag or mineral powder, such as patent CN202311100831.1 discloses a high-strength all-solid waste cementitious material and its preparation method and application. The patent uses slag powder, steel slag powder, and gypsum as raw materials. The slag powder includes silicon dioxide, magnesium oxide, and calcium oxide. The magnesium oxide is provided by magnesium slag, and the calcium oxide is provided by carbide slag. By modifying the magnesium slag, carbide slag, and steel slag powder, respectively, a high-strength all-solid waste cementitious material is obtained. However, there is no relevant report on how to prepare a low-activity mineral powder-based all-solid waste cementitious material that meets the requirements of a 42.5 grade cementitious material with low-activity mineral powder as the main cementitious material by additionally adding a separate modifier.
[0005] Therefore, there is an urgent need for a modifier that can improve the mechanical properties of all-solid waste cementitious materials with low-activity mineral powder as the main cementitious material to solve the above problems. Summary of the invention
[0006] In order to solve the above technical problems, the present invention proposes a modifier for low-activity mineral powder-based all-solid waste cementitious materials and a preparation method thereof.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] The invention provides a modifier for low-activity mineral powder-based all-solid waste cementitious material. The modifier comprises the following components, measured by the amount added to the low-activity mineral powder-based all-solid waste cementitious material: 0.5-1.2% slaked lime, 1%-5.8% aluminate and 0.5%-1.4% polyaluminium chloride.
[0009] Preferably, the content of calcium hydroxide in the slaked lime is above 95%.
[0010] Preferably, the aluminate includes one or more of sulphoaluminate cement and ferroaluminate cement.
[0011] Preferably, the polymerization degree of the polyaluminium chloride is 4-8 and the basicity is 40-90.
[0012] The present invention provides a method for preparing a modifier for low-activity mineral powder-based all-solid waste cementitious materials described in the above technical solution, comprising the following steps: weighing slaked lime, aluminate and polyaluminium chloride in proportion and mixing the three to obtain the modifier for low-activity mineral powder-based all-solid waste cementitious materials.
[0013] The present invention provides a low-activity mineral powder-based all-solid waste cementitious material, which comprises the following components in parts by weight:
[0014] 247.5-288 parts of active mineral powder, 67.5-90 parts of desulfurized gypsum, 58.5-81 parts of fly ash and 31.5-36 parts of the modifier described in the above technical solution.
[0015] The present invention provides a low-activity mineral powder-based all-solid waste mortar, which comprises the following components in parts by weight: 247.5 to 288 parts of low-activity mineral powder, 67.5 to 90 parts of desulfurized gypsum, 58.5 to 81 parts of fly ash, 31.5 to 36 parts of the modifier described in the above technical solution, 1,350 parts of sand and 225 parts of water.
[0016] The present invention provides a method for preparing the low-activity mineral powder-based all-solid waste mortar described in the above technical solution, comprising the following steps:
[0017] (1) mixing low-activity mineral powder, desulfurized gypsum and fly ash and stirring to obtain a base material;
[0018] (2) mixing slaked lime, aluminate and polyaluminium chloride uniformly to obtain a modifier;
[0019] (3) After the base material obtained in step (1) and the modifier obtained in step (2) are evenly mixed, sand is added, and then water is added and stirred evenly, and then the mixture is formed and cured to obtain the low-activity mineral powder-based all-solid waste mortar.
[0020] Preferably, in step (1), the low-activity mineral powder, desulfurization gypsum and fly ash also include a grinding step before mixing; the grinding time of the low-activity mineral powder is 3 hours, the grinding time of the desulfurization gypsum is 1 hour, and the grinding time of the fly ash is 0.5 hours.
[0021] Preferably, in step (3), the curing temperature is 20° C., the curing humidity is 90%, and the curing time is 3 to 28 days.
[0022] Compared with the prior art, the present invention has the following advantages and technical effects:
[0023] The present invention uses slaked lime, aluminate and polyaluminium chloride as raw materials to prepare a modifier for low-activity mineral powder-based all-solid waste cementitious materials, wherein the polyaluminium chloride and aluminate can supplement the aluminum element, which accounts for a relatively small proportion in the low-activity mineral powder, and improve the 28d activity of the low-activity mineral powder, thereby improving the mechanical properties of the low-activity mineral powder-based all-solid waste cementitious materials. The modifier provided by the present invention can be added in small amounts as a chemical additive to mortar or concrete with low-activity mineral powder as the main cementitious material, which can greatly improve the mechanical properties of the low-activity mineral powder-based all-solid waste cementitious materials. The modified cementitious materials can be used in cement-stabilized crushed stone layers of road surfaces, and can also be used to prepare mine filling cementitious materials for use in mine filling.
[0024] The raw materials of the modifier provided by the present invention are easy to obtain and require few types, with a wide selection range and strong universality. By adjusting the ratio between the raw materials to design a specific modifier, the problems of low mechanical properties of the current low-activity mineral powder-based all-solid waste cementitious materials 28d and poor workability and high cost during the construction process can be effectively alleviated, and the utilization rate of the low-activity mineral powder as a geopolymer material can be indirectly improved.
[0025] The raw material source of the modifier provided by the present invention is similar to that of cement admixtures, the cost is controllable, and the preparation method and application method are simple and efficient, no special equipment is required, and labor and energy consumption costs are saved. In addition, it has the characteristics of convenience, high efficiency, small dosage, and obvious modification effect, greatly increases the utilization rate of solid waste, improves the mechanical properties of low-activity mineral powder-based all-solid waste cementitious materials, and achieves the purpose of energy saving and emission reduction.
[0026] The modifier provided by the present invention can be used to modify low-activity mineral powder-based all-solid waste cementitious materials, and can also be used to improve the mechanical properties of low-activity mineral powder activity, while the prior art does not have a modifier for low-activity mineral powder-based all-solid waste cementitious material systems. The modifier provided by the present invention can be used alone or in combination with other organic / inorganic multifunctional admixtures, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0028] Figure 1 The line graphs of the 3d, 7d and 28d compressive strength and flexural strength of the low-activity mineral powder-based all-solid waste mortar in Application Example 2;
[0029] Figure 2 The line graphs of the 3d, 7d and 28d compressive strength and flexural strength of the low-activity mineral powder-based all-solid waste mortar in Application Example 3;
[0030] Figure 3 This is the line graph of the 3d, 7d and 28d compressive strength and flexural strength of the low-activity mineral powder-based all-solid waste mortar in Application Example 4. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0033] An embodiment of the present invention provides a modifier for a low-activity mineral powder-based all-solid waste cementitious material. Calculated by the amount added to the low-activity mineral powder-based all-solid waste cementitious material, the modifier includes the following components: 0.5% to 1.2% slaked lime, 1% to 5.8% aluminate and 0.5% to 1.4% polyaluminium chloride.
[0034] The present invention uses slaked lime, aluminate and polyaluminium chloride as raw materials to prepare a modifier for a low-activity mineral powder-based all-solid waste cementitious material, wherein the polyaluminium chloride and aluminate can supplement the aluminum element, which accounts for a relatively small proportion in the low-activity mineral powder, and improve the 28d activity of the low-activity mineral powder, thereby improving the mechanical properties of the low-activity mineral powder-based all-solid waste cementitious material, and the slaked lime can provide an alkaline environment for the dissolution of its active components.
[0035] In a preferred embodiment, the modifier includes 0.5% to 1.2% slaked lime, more preferably 1.2%, based on the amount added to the low-activity mineral powder-based all-solid waste cementitious material. The present invention controls the amount of slaked lime within the above range, which has the advantages of low dosage and high efficiency activation. Too much slaked lime will cause its hydration reaction product to be wrapped on the particle surface and affect further reaction, while too little slaked lime will affect the dissolution of active components.
[0036] In a preferred embodiment, the content of calcium hydroxide in the slaked lime is above 95%.
[0037] In a preferred embodiment, the modifier includes 1% to 5.8% aluminate, and more preferably 5.6% aluminate, in terms of the amount added to the low-activity mineral powder-based all-solid waste cementitious material. The present invention controls the amount of aluminate within the above range, which has the advantage of high activity. Too much aluminate will affect the reaction, and too little low-activity mineral powder will not achieve the required activity.
[0038] In a preferred embodiment, the aluminate includes one or more of sulphoaluminate cement and ferroaluminate cement, and more preferably sulphoaluminate cement.
[0039] In a preferred embodiment, the modifier includes 0.5% to 1.4% polyaluminium chloride, and more preferably 1.2%, based on the amount added to the low-activity mineral powder-based all-solid waste cementitious material. The present invention controls the amount of polyaluminium chloride within the above range, which has the advantage of high activity. Too much polyaluminium chloride will affect the reaction, and too little low-activity mineral powder will not achieve the required activity.
[0040] In a preferred embodiment, the degree of polymerization of the polyaluminium chloride is 4 to 8, and the basicity is 40 to 90. The present invention uses polyaluminium chloride with a degree of polymerization and basicity within the above ranges, which is beneficial to improving the mechanical properties of low-activity mineral powder-based all-solid waste cementitious materials.
[0041] The present invention provides a method for preparing a modifier for low-activity mineral powder-based all-solid waste cementitious materials described in the above technical solution, comprising the following steps: weighing slaked lime, aluminate and polyaluminium chloride in proportion and mixing the three to obtain the modifier for low-activity mineral powder-based all-solid waste cementitious materials.
[0042] The preparation method of the modifier for low-activity mineral powder-based all-solid waste gelling material provided by the invention is simple to operate, highly efficient, does not require special equipment, and saves labor and energy consumption.
[0043] The present invention provides a low-activity mineral powder-based all-solid waste cementitious material, which comprises the following components in parts by weight: 247.5 to 288 parts of low-activity mineral powder, 67.5 to 90 parts of desulfurized gypsum, 58.5 to 81 parts of fly ash and 31.5 to 36 parts of the modifier described in the above technical solution.
[0044] The low-activity mineral powder-based all-solid waste cementitious material provided by the present invention uses low-activity mineral powder as the main raw material, and utilizes desulfurization gypsum, a by-product of wet desulfurization of flue gas in power plants, and fly ash, a main solid waste generated by coal mining and coal-fired power generation, and combines the use of a modifier to obtain a low-activity mineral powder-based all-solid waste cementitious material with excellent mechanical properties, which provides theoretical support and core technology for the harmless disposal, large-scale utilization and waste ecological environment management of low-activity mineral powder, desulfurization gypsum and fly ash.
[0045] In a preferred embodiment, the content of aluminum in the low-activity mineral powder is 10.65%, and the content of silicon is 24.49%.
[0046] The present invention provides a low-activity mineral powder-based all-solid waste mortar, which comprises the following components in parts by weight: 247.5 to 288 parts of low-activity mineral powder, 67.5 to 90 parts of desulfurized gypsum, 58.5 to 81 parts of fly ash, 31.5 to 36 parts of the modifier described in the above technical solution, 1,350 parts of sand and 225 parts of water.
[0047] The invention adds water and sand on the basis of low-activity mineral powder, desulfurized gypsum, fly ash and a modifier, thereby obtaining low-activity mineral powder-based all-solid waste mortar with excellent mechanical properties.
[0048] The present invention provides a method for preparing the low-activity mineral powder-based all-solid waste mortar described in the above technical solution, comprising the following steps:
[0049] (1) mixing low-activity mineral powder, desulfurized gypsum and fly ash and stirring to obtain a base material;
[0050] (2) mixing slaked lime, aluminate and polyaluminium chloride uniformly to obtain a modifier;
[0051] (3) After the base material obtained in step (1) and the modifier obtained in step (2) are evenly mixed, sand is added, and then water is added and stirred evenly, and then the mixture is formed and cured to obtain the low-activity mineral powder-based all-solid waste mortar.
[0052] In a preferred embodiment, in step (1), the low-activity mineral powder, desulfurized gypsum and fly ash further include a grinding step before mixing; the grinding time of the low-activity mineral powder is 3 hours, the grinding time of the desulfurized gypsum is 1 hour, and the grinding time of the fly ash is 0.5 hours. The present invention reduces the particle size of the low-activity mineral powder, desulfurized gypsum and fly ash by grinding, thereby improving their activity.
[0053] In a preferred embodiment, in step (1), the stirring temperature is 20-25°C.
[0054] In a preferred embodiment, in step (3), the water is added at a uniform speed to prevent the slurry from splashing out.
[0055] In a preferred embodiment, in step (3), the molding time is 24 hours; the mold used for the molding is a 40mm×40mm×160mm mortar specimen triple mold.
[0056] In a preferred embodiment, in step (3), the curing temperature is 20° C., the curing humidity is 90%, and the curing time is 3 to 28 days.
[0057] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.
[0058] In the following application examples and comparative application examples, the low-activity mineral powder comes from Baotou City, and the aluminum content is 10.65% and the silicon content is 24.49%;
[0059] Sulphoaluminate cement was purchased from Tangshan Polar Bear Building Materials Co., Ltd.
[0060] Example 1
[0061] A modifier for low-activity mineral powder-based all-solid waste cementitious material, wherein the modifier is composed of the following components, based on the amount added to the low-activity mineral powder-based all-solid waste cementitious material: 1.2% slaked lime, 5.6% sulphoaluminate cement and 1.2% polyaluminium chloride;
[0062] Among them, the content of calcium hydroxide in slaked lime is 95%; the degree of polymerization of polyaluminium chloride is 8, and the basicity is 40.
[0063] Example 2
[0064] A modifier for low-activity mineral powder-based all-solid waste cementitious material, wherein the modifier is composed of the following components, based on the amount added to the low-activity mineral powder-based all-solid waste cementitious material: 1.2% slaked lime, 5.0% sulphoaluminate cement and 1.4% polyaluminium chloride;
[0065] Among them, the content of calcium hydroxide in slaked lime is 95%; the degree of polymerization of polyaluminium chloride is 8, and the basicity is 40.
[0066] Example 3
[0067] A modifier for low-activity mineral powder-based all-solid waste cementitious material, wherein the modifier is composed of the following components, based on the amount added to the low-activity mineral powder-based all-solid waste cementitious material: 1.0% slaked lime, 5.0% sulphoaluminate cement and 1.1% polyaluminium chloride;
[0068] Among them, the content of calcium hydroxide in slaked lime is 95%; the degree of polymerization of polyaluminium chloride is 8, and the basicity is 40.
[0069] Example 4
[0070] A modifier for low-activity mineral powder-based all-solid waste cementitious material, wherein the modifier is composed of the following components, based on the amount added to the low-activity mineral powder-based all-solid waste cementitious material: 1.0% slaked lime, 5.8% sulphoaluminate cement and 1.1% polyaluminium chloride;
[0071] Among them, the content of calcium hydroxide in slaked lime is 95%; the degree of polymerization of polyaluminium chloride is 8, and the basicity is 40.
[0072] Example 5
[0073] A modifier for low-activity mineral powder-based all-solid waste cementitious material, wherein the modifier is composed of the following components, based on the amount added to the low-activity mineral powder-based all-solid waste cementitious material: 1.2% slaked lime, 5.0% sulphoaluminate cement and 1.1% polyaluminium chloride;
[0074] Among them, the content of calcium hydroxide in slaked lime is 95%; the degree of polymerization of polyaluminium chloride is 8, and the basicity is 40.
[0075] Application Example 1
[0076] A low-activity mineral powder-based all-solid waste cementitious material, comprising the following components: 288 g of low-activity mineral powder, 67.5 g of desulfurized gypsum, 58.5 g of fly ash and 36 g of the modifier in Example 1;
[0077] The preparation process of low-activity mineral powder-based all-solid waste cementitious materials is as follows:
[0078] (1) 288 g of low-activity mineral powder, 67.5 g of desulfurized gypsum and 58.5 g of fly ash were mixed in a stirring pot and stirred at room temperature to obtain a base material;
[0079] (2) 5.4 g of slaked lime, 25.2 g of sulphoaluminate cement and 5.4 g of polyaluminium chloride were mixed uniformly to obtain a modifier;
[0080] (3) The modifier obtained in step (2) was added to a stirring pot and mixed evenly with the base material in step (1), and then 225 g of tap water was added at a uniform rate. After stirring for 4 min, three mortar test blocks of 40 mm × 40 mm × 160 mm were placed in the mold. After 24 h of molding, the molds were demolded and the test blocks were placed in a curing room at 20°C and 90% humidity for 3 d, 7 d and 28 d.
[0081] Application Example 2
[0082] A low-activity mineral powder-based all-solid waste mortar, composed of the following components: 288g of low-activity mineral powder, 67.5g of desulfurized gypsum, 58.5g of fly ash, 36g of the modifier in Example 1, 1350g of sand and 225g of water;
[0083] The preparation process of low-activity mineral powder-based all-solid waste mortar is as follows:
[0084] Steps (1) to (2) are the same as those in Application Example 1;
[0085] (3) Add the modifier obtained in step (2) into a stirring pot and mix it evenly with the base material in step (1), then place the stirring pot on a fully automatic mortar mixer, and then add 1350 g of standard sand; turn on the fully automatic mortar mixer, and under low-speed stirring, uniformly add 225 g of tap water into the stirring pot, stir for 4 minutes, and then put in three molds of 40 mm × 40 mm × 160 mm mortar test blocks, demold after 24 hours of molding, and place the test blocks in a curing room at 20°C and 90% humidity for 3 days, 7 days and 28 days.
[0086] Application Examples 3 to 6
[0087] The difference from Application Example 2 is that the modifier in Example 1 is replaced by the modifiers in Examples 2 to 5, and the rest is the same as Application Example 2.
[0088] Comparative application example 1
[0089] The difference from Application Example 2 is that no modifier is added, and the rest is the same as Application Example 2.
[0090] According to GB / T 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)", the 3d, 7d and 28d compressive strength and flexural strength of Application Examples 2 to 6 and Comparative Example 1 were tested. The test results are shown in Figures 1 to 3 and Table 1.
[0091] Figures 1 to 3 The following is a line chart of the 3d, 7d and 28d compressive strength of low-activity mineral powder-based all-solid waste mortar in application examples 2 to 4. Figures 1 to 3It can be seen that adding the modifier provided by the present invention to the low-activity mineral powder-based all-solid waste mortar can significantly improve the mechanical properties of the low-activity mineral powder-based all-solid waste mortar, and the strength grade reaches 42.5 when it is cured to 28 days. In particular, the mechanical properties of the low-activity mineral powder-based all-solid waste mortar from 3d to 7d increase faster, indicating that the mineral powder-based all-solid waste mortar with the modifier can obtain better mechanical properties at an early stage, indicating that the modifier provided by the present invention has excellent modification effect.
[0092] Table 1 3d, 7d and 28d compressive strength and flexural strength of application examples 2 to 6 and comparative example 1
[0093]
[0094] It can be seen from Table 1 that the mechanical properties of the mortar prepared using the modifier in Example 1 are optimal.
[0095] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A modifier for low-activity mineral powder-based all-solid waste cementitious materials, characterized in that: Calculated by the addition amount in the low-activity mineral powder-based all-solid waste cementitious material, the modifier includes the following components: 0.5% to 1.2% slaked lime, 1% to 5.8% aluminate and 0.5% to 1.4% polyaluminium chloride.
2. The modifier for low-activity mineral powder-based all-solid waste gelling material according to claim 1, characterized in that: The content of calcium hydroxide in the slaked lime is above 95%.
3. The modifier for low-activity mineral powder-based all-solid waste cementitious materials according to claim 1, characterized in that: The aluminate includes one or more of sulphoaluminate cement and ferroaluminate cement.
4. The modifier for low-activity mineral powder-based all-solid waste gelling material according to claim 1, characterized in that: The polymerization degree of the polyaluminium chloride is 4-8, and the basicity is 40-90.
5. A method for preparing a modifier for low-activity mineral powder-based all-solid waste cementitious materials according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: weighing slaked lime, aluminate and polyaluminium chloride in proportion and mixing the three to obtain the modifier for low-activity mineral powder-based all-solid waste gelling material.
6. A low-activity mineral powder-based all-solid waste cementitious material, characterized in that: The invention comprises the following components by weight: 247.5 to 288 parts of low-activity mineral powder, 67.5 to 90 parts of desulfurized gypsum, 58.5 to 81 parts of fly ash and 31.5 to 36 parts of the modifier described in any one of claims 1 to 4.
7. A low-activity mineral powder-based all-solid waste mortar, characterized in that: The invention comprises the following components by weight: 247.5 to 288 parts of low-activity mineral powder, 67.5 to 90 parts of desulfurized gypsum, 58.5 to 81 parts of fly ash, 31.5 to 36 parts of the modifier according to any one of claims 1 to 4, 1350 parts of sand and 225 parts of water.
8. A method for preparing the low-activity mineral powder-based all-solid waste mortar according to claim 7, characterized in that: The following steps are involved: (1) mixing low-activity mineral powder, desulfurized gypsum and fly ash and stirring to obtain a base material; (2) mixing slaked lime, aluminate and polyaluminium chloride uniformly to obtain a modifier; (3) After the base material obtained in step (1) and the modifier obtained in step (2) are evenly mixed, sand is added, and then water is added and stirred evenly, and then the mixture is formed and cured to obtain the low-activity mineral powder-based all-solid waste mortar.
9. The preparation method according to claim 8, characterized in that: In step (1), the low-activity mineral powder, desulfurization gypsum and fly ash also include a grinding step before mixing; the grinding time of the low-activity mineral powder is 3 hours, the grinding time of the desulfurization gypsum is 1 hour, and the grinding time of the fly ash is 0.5 hours.
10. The preparation method according to claim 8, characterized in that: In step (3), the curing temperature is 20° C., the curing humidity is 90%, and the curing time is 3 to 28 days.
Citation Information
Patent Citations
Gelatinizing agent suitable for unclassified tailing filling
CN103086620A
Low-clinker aluminate cementing material for sewage pipeline
CN112694306A
Method for exciting activity of cement mixed material by using sulfate
CN113121137A
All-solid-waste-based low-carbon green ecological cementing material and manufacturing method thereof
CN115321848A
Alkali-activated all-solid waste seawater sea sand coral concrete for island reef and preparation process thereof
CN116217193A
